I = ∫ e^(2x).dx
Let u = 2x
du/dx = 2
dx = du / 2
I = (1/2).∫ e^(u).du
I = (1/2).e^(u) + C
I = (1/2).e^(2x) + C
2007-04-30 22:08:08
·
answer #1
·
answered by Como 7
·
0⤊
0⤋
I believe its 1/2 e^2x. Taking that derivative gives 1/2 e^2x(2) = e^2x.
2007-04-30 23:24:58
·
answer #2
·
answered by spmdrumbass 4
·
0⤊
0⤋
integral e^(2x) dx
Let u = 2x. Then du/dx = 2 ==> dx = du/2
integral e^u du/2 = (1/2) integral e^u du = (1/2)e^u + C = (1/2)e^(2x) + C
2007-04-30 23:25:12
·
answer #3
·
answered by DavidK93 7
·
2⤊
0⤋
e^u du = e^u
thus integral [e^2x]dx = 1/2[e^2x]2dx = 1/2e^2x
2007-04-30 23:26:20
·
answer #4
·
answered by mikedotcom 5
·
0⤊
0⤋
(1/2)e^(2x) + c
2007-04-30 23:25:19
·
answer #5
·
answered by gudspeling 7
·
2⤊
0⤋
(e^2x)/2 + c
2007-04-30 23:26:03
·
answer #6
·
answered by Superconductor 3
·
0⤊
0⤋
(e^2x)/2. Verify this for yourself that e^(nx) has antiderivative [e^(nx)]/n for all n, using u-substitution.
2007-04-30 23:25:50
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋